GAMBARAN FAKTOR KEGAGALAN BERHEMTI MEROKOK PADA REMAJA PUTRI DI SMK WILAYAH KERJA PUSKESMAS SRONDOL - Ningsih, Purwati; Husodo, Besar Tirto; Kusumawati, Aditya (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2020)
Smoking in adolescents is more prone to experiencing serious health problems because it is at an age of growth. Negative impact on health and emotional. Purpose of this study was to describe the description of failure factor to stop smoking of the teenagers in vocational school of the Srondol Health Center. This research is a quantitative study and uses a cross sectional approach. Questionnaire interviews were conducted on 36 respondents with total sampling technique. Data analysis was performed univariately. Results of this study indicate that respondents were 17 years old (33.3%). Many as 86.1% of respondents were old smokers. Younger the age when smoking starts the more likely the respondents are to become heavy smokers and more difficult it is to stop smoking behavior. Respondents with a vocational high school education grade XI (58.3%) and have an allowance per month above an average (61.1%), the respondent's allowance is obtained from parents, siblings and from the results of part time work. Pocket money obtained from several sources can meet the needs of respondents who can be used to buy cigarettes. Most respondents have good knowledge (80.6%), good attitude (52.8%), the availability of available cigarettes (55.6%) and affordable affordability of cigarettes (61.1%), more and easier facilities or places to get cigarettes, the higher the likelihood of someone to fail to stop smoking. Respondents who are aware of the KTR policy at school (88.9%), have support from parents who support (69.4%), support from friends who support (66.7%) and support from teachers who support (80.6%). Stopping smoking behavior for those who are addicted is difficult to stop, because some of the characteristics respondents still do not care about the environment even with their family members sharing cigarettes. Suggestion for schools is that they need to monitor the environment around the school so that students do not easily reach cigarette buying and selling transactions.